Major challenges ahead for Hungarian healthcare. (7th December 2011) - Gaál, Péter; Szigeti, Szabolcs; Panteli, Dimitra; Gaskins, Matthew; Ginneken, Ewout van
Abstract : The health sector in Hungary is facing its most serious crisis since the fall of the communist regime. Péter Gaál and colleagues discuss the challenges and how to respond to them